Media Pembelajaran Interaktif Lectora Inspire sebagai Inovasi Pembelajaran - Norma Dewi Shalikhah (Universitas Muhammadiyah Surakarta, 2017)
AbstractThe utilization of information and communication technology in education sector is a tremendous output. Support of ICT is hoped to become an innovation in learning with many involving information technology components inside. Therefore, in globalization era, education sector can not pass from its extent, with involves the inherent technology can produce a system of education. This paper discusses the interactive learning media that involve education technology using lectora inspire application. Lectora inspire is designed specifically for the beginner with purpose user friendly to use to make learning media, and can make the material test or evaluation. The development of interactive learning media with lectora inspire is conducted with how to provide training to the teachers in the elementary school. The methods are done with phases, includes gathering information, planning tools, implementing, presenting and reflecting. The object of this training is MIM Jagalan and MIM Jumoyo Greeting sub Magelang regency.Keywords: Media Interactive Learning, Lectora Inspire, Learning Innovation